2015
DOI: 10.20344/amp.6257
|View full text |Cite
|
Sign up to set email alerts
|

Conhecer a Diversidade do Vírus da Hepatite C para Além da Frequência dos Genótipos em Amostras Analisadas entre 2009 e 2014 no Laboratório de Referência do Instituto Nacional de Saúde Dr. Ricardo Jorge

Abstract: Acta Med Port 2015 Nov-Dec;28(6):695-701 RESUMOIntrodução: A identificação dos genótipos do vírus da hepatite C foi essencial para o prognóstico e tratamento dos doentes crónicos durante os últimos anos. Foram objetivos deste estudo conhecer a frequência de genótipos do vírus da hepatite C nos últimos seis anos, e revelar o contributo de um ensaio in-house para caracterização molecular do vírus. Material e Métodos:A genotipagem do vírus da hepatite C por LiPA foi realizada em 923 amostras, maioritariamente pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The most common subtypes that infect these IDU were 1a (52.4%) and 3a (20.2%-21.4%), which is in accordance with previous studies [ 12 ]. These subtypes are also frequent in infected IDU in several European countries [ 10 ]. Of note, in the studied population, 32 individuals reported that they excessively consume alcohol, which negatively impacts on liver diseases and favors the progression of HCV infections [ 28 ], and at least 24 individuals had advanced fibrosis or cirrhosis, making them more likely to fail treatment with DAAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common subtypes that infect these IDU were 1a (52.4%) and 3a (20.2%-21.4%), which is in accordance with previous studies [ 12 ]. These subtypes are also frequent in infected IDU in several European countries [ 10 ]. Of note, in the studied population, 32 individuals reported that they excessively consume alcohol, which negatively impacts on liver diseases and favors the progression of HCV infections [ 28 ], and at least 24 individuals had advanced fibrosis or cirrhosis, making them more likely to fail treatment with DAAs.…”
Section: Discussionmentioning
confidence: 99%
“…Although methadone programs have been successfully implemented, Portugal is one of the European countries that has reported higher rates of hepatitis C infection in drug users, varying from 60.0% to 80.0% [ 10 , 11 ]. This population is especially vulnerable because of their risky behaviors and usually do not adhere to conventional healthcare facilities for the treatment of hepatitis C. In a study conducted on a population of drug users attending a low-threshold methadone program in Lisbon, the prevalence of HCV antibodies was 67.6%, and RNA viral load was detected in 68.4% of the enrolled individuals [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The epidemiological pattern of HCV genotypes in Portugal reveals a GT 1 prevalence of approximately 53-60% followed by 25-34% for GT 3 and 7-9% for GT 4. GT 2 is the less frequent, with a prevalence not exceeding 2.3% [13,14].…”
Section: Introductionmentioning
confidence: 94%